Evaluation of antibiotic resistance patterns and heavy metals tolerance of some bacteria isolated from contaminated soils and sediments from Warri, Delta State, Nigeria - A.F. Eghomwanre; N.O. Obayagbona; O Osarenotor; B.J. Enagbonma (Journal of Applied Sciences and Environmental Management, 2016)
This work investigated the antibiotic resistance patterns and heavy metals such as Lead (Pb), Zinc (Zn), Cadmium (Cd) and iron (Fe) tolerance of selected bacteria isolated from contaminated soils and sediments around Warri area of Delta State. The heterotrophic bacterial counts for the sampled soils and sediments ranged from 1.7×105 cfu/g to 5.7×105cfu/g for Ubeji river sediments, 1.0×105 cfu/g to 9.0×105cfu/g for spare parts dumpsite and 1.2×104cfu/g to 9.0×104 cfu/g for Ifie depot sites respectively. The characterized bacterial isolates included; Klebsiella sp, Bacillus subtilis, Streptococcus sp., Escherichia coli, Klebsiella mobilis and Staphylococcus sp., Micrococcus sp. and Pseudomonas aeroginosa. Bacterial isolates showed multiple drug resistance and the most resistant isolates were S. aureus, E. coli and P. aeroginosa while K. mobilis exhibited the least resistance. The tolerance of the bacterial isolates exposed to varying concentrations of Pb2+, Cd2+, Fe2+, and Zn2+was ascertained using agar diffusion method. All the bacterial isolates exhibited varying degree of susceptibility at different concentrations of Pb and Cd while the organisms displayed abundant and moderate growth in the presence of Fe and Zn even at higher concentrations. The ability of these bacteria to resist antibiotics and heavy metal tolerance could present serious danger to the environment as the resistance genes may be transferred to surrounding wild type microbial cells.